Comunicação e complexidade: o discurso mítico do SBT - Freitas, Fernanda Lopes de (2012)
The pursuit of knowledge tied to our personal journey, seems to be a indispensable for our particular building at all levels, both as academics, professionals and even social. To understand this space for dialogue between individuals and products that we offer organizations and at the same time, in turn, seem to encourage us to write this and the knowledge in this area through a variety of knowledge. In this paper, we study the complexity of organizational Miths of Discoursers on SBT, at levels both verbally and nonverbally. As well, we will seek to understand and explain the relationships that occur with mythical object of our analysis. For this, the readings of the speeches will be made through institutional selected six parts, which together with the a priori categories and the methodology chosen and method used, will enable our study. The pre-established concepts for the scientific construction of this mosaic are: Comunication, from Morin, and this subcategory Stereotype, from Barthes; Public Relations, from Simões, and subfields: Brand, of Semprini, Strategic Positioning of Ries&Trout, and Dimingo, under the Public, Rabaça approaches and França, and Organization, also anchored by Morin; Charisma, by Weber; Power, Myth, Sociolect anchored by Barthes. However in order to gide the composition of our knowledge, we have the Paradigm of Complexity, of Morin as a method, the Semiology as a technique, made possible in a Semiology, Barthes both. So we try to understand explain these relationships that the organizational and discursive Myths in evidence, and yhat gives us so much restlessness, hungry for answers, even if temporary. Thus, we want to end, show how necessary for Communication, writing is the news knowledge in a transdiciplinary way.